Imaging in Movement Disorders: A Clinician's Perspective on Novel Applications - Smith, Kara M.; Saranathan, Manojkumar (Seminars in Neurology, 2025)
The utility of neuroimaging in the diagnosis and management of movement disorders has been steadily increasing as both imaging and image analysis technologies have advanced in the last decade. Neuroimaging is also playing a critical role in the search for novel therapies to prevent, slow down, and treat various movement disorders. This article reviews both standard and innovative imaging tools available for both clinicians and researchers. We focus predominantly on the clinician's perspective, discussing imaging tools that are becoming rapidly available and how these may be integrated into the clinic to provide cutting-edge and patient-centered care. We discuss novel and emerging techniques and their potential implications for the field, as well as highlight areas still in need of imaging solutions.
Keywords: diagnostic imaging; MRI; molecular imaging; movement disorders